2021
DOI: 10.4018/jgim.20211101.oa38
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Social Networks to Globalize and Popularize Product Brands in Different Cultural Areas

Abstract: The purpose of this paper is to investigate the influential factors of online social network advertising in three different cultural areas, being China, India, and the US. This study uses the Social Capital Theory (SCT), and Guanxi Theory, as two types of relation theories; then collects data from the virtual community (or online social network, VC) members of three different areas, a total of 730 valid surveys were completed for model testing. The findings show that: (1) building the relationship dimension of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The research found that post popularity plays an essential role in persuading users through both central and peripheral routes (Chang et al, 2021). This research shows that on social network sites, argument quality, post popularity, and attractiveness reinforce usefulness and preference, which in turn lead to 'Like Intention' and 'Share Intention'.…”
Section: I'd Watch Something Really Interesting Even If It's Sponsore...mentioning
confidence: 81%
See 1 more Smart Citation
“…The research found that post popularity plays an essential role in persuading users through both central and peripheral routes (Chang et al, 2021). This research shows that on social network sites, argument quality, post popularity, and attractiveness reinforce usefulness and preference, which in turn lead to 'Like Intention' and 'Share Intention'.…”
Section: I'd Watch Something Really Interesting Even If It's Sponsore...mentioning
confidence: 81%
“…The high SNS usage thus can be attributed to both news as well as entertainment. In addition to these, SNSs provide a platform for people to interact with members sharing similar interests (Chang & Wu, 2021). Many of the participants mentioned that they were a part of one group or another on these platforms.…”
Section: Resultsmentioning
confidence: 99%